Answer:
it is x= 0
Explanation:
you distribute the numbers in the parentheses first so your new equation would be 12 - 8x = 3x + 12 (basically multiply 3 by what was in the parentheses)
then cancel equal terms so 12 - 8x = 3x + 12 becomes -8x = 3x
after that move the variable and the 3 to the left while changing the sign from + to - (the + sign is implied since it's a positive number) your new equation becomes -8x - 3x = 0
next collect like terms so the numbers with the same variable meaning subtract -8x - 3x also known as -8x + -3x creating the equation -11x =0
finally divide both sides of the equation -11x = 0 by -11 creating x=0